Estrutura da assembléia de Gerromorpha (Heteroptera) em Igarapés dos Municípios de Rio Preto da Eva e Manaus, Amazonas - Godoy, Bruno Spacek (Instituto Nacional de Pesquisas da Amazônia - INPA, 2007)
The members of the Gerromorpha assemblage (Heteroptera: Insecta) were collected in 32 streams in central Amazonia in the counties of Rio Preto da Eva and Manaus, Amazonas, in four sub-basins of the Rio Negro and Lower Amazon from April to August 2004. In parallel with the collection process, a protocol was developed in order to describe the structure of the habitat of the stream. The Cuieiras River basin had the largest number of species: 22 out of the total of 30 collected. These were distributed in the families Gerridae, Veliidae, Hydrometidae and Mesoveliidae. No significant relationship was found between the structure of the habitat and the increase in the number of species. The Mantel test indicated that the environmental parameters examined are not correlated with physical distance. Three other Mantel tests indicated that the Gerromorpha assemblage is related both to the environmental change registered using the protocol and to the physical distance between the sampled points, as much for each variable separately as in set. To determine whether habitat influences occurrence of these species, models were used that calculated the maximum likelihood for the data collected, using the environmental characteristics as variables. Seventeen species were selected for inclusion in these models, only six (40%) they had presented models including ambient variable as better describing for your occurrence. Sixty percent of the tested species were not well explained by models that included environmental covariables. Factors such as the effect of mass and of biotic interactions among the species can act as "noise" in models that explain the occurrence of the species taking into account the rela tionship of the organism to its habitat. One explanation to related to mass effect mass allowed species that are not adapted to environmental conditions of a given stream to be present anyway due to migration from places where a viable population exists. An effect of this type was observed when we took into account the relationship between the proximity of the points and the similarity of the assemblage. Thus, the Gerromorpha assemblage in the region of the central Amazônia stream is related with the structure of the habitat, where different species possess functions of distinct occurrences.
Keywords: Insetos aquáticos; Heteroptera; Gerromorfha